PENGARUH PERSEPSI HARGA DAN KUALITAS LAYANAN TERHADAP MINAT BELI ULANG JASA CUCI SEPATU (STUDI PENELITIAN PADA JASA LAUNDRY SEPATU KUSUMASHOESCARE DI KARANGASEM) - I Gede Bayu Kusuma; I Gusti Agung Ngurah Gede Eka Teja Kusuma; I Wayan Gede Antok Setiawan Jodi (VALUES, 2022)
Fostering buying interest and ultimately evoking the intention to repurchase service products is not easy. There are several factors that can influence it, two of which are service quality and price. The purpose of this study was to determine the effect of price perception and service quality on repurchase interest at Kusumashoescare Karangasem. The population in this study are all Kusumashoescare customers who live in Karangasem aged 18 years and over who have made purchases of service products more than twice. The sampling technique used purposive sampling method with a total sample of 100 people. Data collection techniques using a questionnaire that has been tested for validity and reliability. The data analysis technique used to answer the hypothesis is multiple linear regression analysis. The results of this study indicate that price perception has a significant negative effect on repurchase interest at Kusumashoescare Karangasem and service quality has a significant positive effect on repurchase interest at Kusumashoescare Karangasem.